2011
DOI: 10.1017/s1751731111001029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of smallholder farmers and pastoralists’ preferences for sheep breeding traits: choice model approach

Abstract: Identification of breeding objective traits pertinent to specific production environments with the involvement of target beneficiaries is crucial to the success of a breed improvement program. A choice experiment was conducted in four locations representing different production systems and agro-ecologies that are habitat to four indigenous sheep breeds (Afar, Bonga, Horro and Menz) of Ethiopia with the objective of identifying farmers'/pastoralists' preferences for sheep breeding traits. Following a synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 18 publications
6
49
1
Order By: Relevance
“…The Menz farmers also have a clear breeding objective of increasing the market value of their sheep through selection for both appearance (color, horn) and body size/weight traits (Duguma et al, 2011). However, analysis of farmers' traditional breeding practices in the current study showed that there is stagnating or declining trends in body weights.…”
Section: Discussionmentioning
confidence: 62%
“…The Menz farmers also have a clear breeding objective of increasing the market value of their sheep through selection for both appearance (color, horn) and body size/weight traits (Duguma et al, 2011). However, analysis of farmers' traditional breeding practices in the current study showed that there is stagnating or declining trends in body weights.…”
Section: Discussionmentioning
confidence: 62%
“…In Ethiopia, sheep are the second most important livestock species next to cattle [4]. Sheep and goat play an important economic role and make a significant contribution to both domestic and export markets through provision of food (meat and milk) and non-food (manure, skin and wool) products [5,6]. Although sheep and goat plays a significant role in national economy of the country to date the benefit obtained from these livestock are hampered by different constrains.…”
Section: Introductionmentioning
confidence: 99%
“…Low uptake of genetic selection tools among livestock farmers is one of the reasons for the lack of realization of potential genetic gain in breeding programs (Duguma et al, 2011;Nielsen et al, 2013). It has been argued that if the uptake of genetic selection tools is to be maximized, breeding objectives have to take into account farmers' preferences for improvements in animal traits (Sy et al, 1997;Nielsen and Amer, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, 3 methodological approaches have been used to analyze stated farmers' preferences: choice experiments (Bett et al, 2011;Duguma et al, 2011), pairwise comparisons (Byrne et al, 2012), and simpler methods such as ranking traits (Dana et al, 2010;Gizaw et al, 2010). Choice experiments have been widely used to analyze farmers' preferences for animal traits.…”
Section: Introductionmentioning
confidence: 99%